Syntheses and characterizations of cyclotriphosphazenes containing 1-naphthyl derivatives - Ibisoglu, Hanife; Guzel, Ali Metin (Pergamon-Elsevier Science Ltd, 2015)
In the present work, a series of cyclotriphosphazenes containing 1-naphthyl derivatives (3, 4, 5, 7, 8 and 9) was synthesized. Mono-(3), geminal bis-(4) and tetrakis (5) 1-naphthylamino substituted cyclotriphosphazenes were synthesized from the reactions of hexachlorocyclotriphosphazene (N3P3Cl6) with 1-naphthylamine. Geminal bis-(7), tetrakis (8) and hexakis (9) 1-thionaphthoxy derivatives were obtained from the reactions of N3P3Cl6 with 1-naphthylthiol. The structures of the compounds (3, 4, 5, 7, 8 and 9) were determined by elemental analysis, mass and (H-1, P-31) NMR spectroscopies. Molecular and crystal structures of 3, 4, 5, 7 and 9 were also characterized by X-ray crystallography. The compounds (3, 5, 7, 8 and 9) were synthesized and characterized for the first time. Compounds 7-9 were reported as the first examples for cyclophosphazenes containing thionapthyl groups in the literature. The crystal structure of compound 4 was reported for the first time. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Cyclophosphazene; 1-Napthylamine; 1-Thionaphthol; P-31 NMR; X-ray